Erratum: The somatic mutation profiles of 2,433 breast cancers refine their genomic and transcriptomic landscapes - Bernard Pereira (Nature Portfolio, 2016)
Nature Communications 7 Article number:11479 (2016); Published: 10 May 2016; Updated: 6 June 2016. The original version of this Article contained an error in the spelling of ‘refine’ in the title of the paper. This has now been corrected in both the PDF and HTML.